National Circular Economic Movement (GESN) Towards Sustainable Development (SDGs) 2030: A Netnography Study - Yusuf, Rolland M (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2025)
Netnography research on the National Circular Economy Movement (GESN) towards Sustainable Development (SDGs) 2030 (Plastic Bottle Waste Management through the Indonesian Plastic Recycling Association or ADUPI) through Instagram social media as an information-generating medium, aims to find out how ADUPI's role in helping build GESN in Indonesia through plastic bottle waste management so that it can achieve the goals of SDGs 2030. The research uses the Netnography method by analyzing data into narrative form. The results showed that ADUPI's big role through GESN since 2018 in waste management with 500 members from various corporate agencies, Sabang to Merauke to achieve the 2030 Sustainable Development Goals with activities that include educating about the problem of plastic bottle waste, direct guidance to waste recycling actors, coordinating with other associations that have similar goals and reporting program achievements.